Diabetic nephropathy in pregnancy: Report of two cases progressing to end-stage renal disease within one year postpartum - Hassan Bin Attique; Deep Phachu; Alexandra Loza; Winston Campbell; Erica Hammer; Ibrahim Elali (Elsevier, 2021)
Background: Diabetes mellitus is a leading cause of nephropathy and end-stage renal disease. However, diabetic nephropathy during pregnancy in patients with normal glomerular filtration rate and subsequent progression to end-stage renal disease has not been well studied. Cases: This report presents two patients with poorly controlled type 1 diabetes mellitus who had diabetic nephropathy with preserved estimated glomerular filtration rate (Case 1: 117 mL/min/1.73m2; Case 2: 79 mL/min/1.73m2) and shared a similar clinical course, with glomerular filtration rates decreasing by approximately one-half during pregnancy and progression to end-stage renal disease within the first year postpartum. Both women had a long history of type 1 diabetes: 18 years and 24 years for case 1 and case 2 respectively. The first patient's course of pregnancy was complicated by difficult-to-control blood glucose and hypertension with subsequent preeclampsia. The second patient's course of pregnancy was complicated by difficult-to-control blood sugars and preterm labor resulting in classical cesarean delivery at 24 weeks. Both patients had renal biopsies shortly after delivery as their renal function continued to worsen postpartum. Both kidney biopsies demonstrated advanced diabetic nephropathy changes and ultimately required chronic renal replacement therapy within 7-9 months postpartum. Conclusion: Comprehensive family planning discussions with women who have diabetic nephropathy should include the risks of renal disease progression, even in those patients with preserved renal function at the time of conception.